2019
DOI: 10.3390/gels5010018
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Photon Upconverting Gels

Abstract: Recent progress in the development of gels showing triplet-triplet annihilation based photon upconversion (TTA-UC) is reviewed. Among the two families of upconverting gels reported, those display TTA-UC based on molecular diffusion show performances comparable to those in solutions, and the TTA-UC therein are affected by dissolved molecular oxygen. Meanwhile, air-stable TTA-UC is achieved in organogels and hydrogels by suitably accumulating TTA-UC chromophores which are stabilized by hydrogen bonding networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…One strategy to avoid this problem is to use viscous droplets, polymers, or co‐assembly of molecular groups as oxygen barriers. [ 49,60 ] However, these methods inevitably slow the diffusion of TTA chromophores or deactivate triplet states and therefore lead to a reduced quantum yield. Third, the TTA process is unlikely to realize deep UV emission due to the limited acceptor singlet energies and strong UV absorptions of organic chromophores and solvents.…”
Section: Materials For Visible‐to‐uv Light Conversionmentioning
confidence: 99%
“…One strategy to avoid this problem is to use viscous droplets, polymers, or co‐assembly of molecular groups as oxygen barriers. [ 49,60 ] However, these methods inevitably slow the diffusion of TTA chromophores or deactivate triplet states and therefore lead to a reduced quantum yield. Third, the TTA process is unlikely to realize deep UV emission due to the limited acceptor singlet energies and strong UV absorptions of organic chromophores and solvents.…”
Section: Materials For Visible‐to‐uv Light Conversionmentioning
confidence: 99%
“…In order to develop photoactive biomaterials that operate by TTA‐UC, it is important to consider the characteristics of the multiexciton system together with the mechanism of upconversion, which has been extensively described in the literature (schematically detailed in Figure S1, Supporting Information). [ 27,28 ] Previous studies have shown that TTA‐UC hydrogels can be synthesized, but none have reported hydrogels containing cells dispersed within a 3D scaffold. [ 15,29 ] In a recent eloquent study, Pluronic‐based gels were simply used as a light source (NIR‐to‐blue light) placed above 2D cultures of hippocampal neurons to trigger optogenetic responses.…”
Section: Resultsmentioning
confidence: 99%
“…However, we note that similar optogenetic responses can be observed in 2D cultures by direct irradiation with blue light. [ 7 ] To obtain biocompatible, cell‐laden TTA‐UC hydrogels, we sought to integrate the sensitizer/annihilator pairs within the core of oil‐in‐water emulsion droplets [ 24,25,28,30,31 ] that could be incorporated into cell‐laden hydrogel matrices (e.g., fibrin gels). Several requirements must be met so that the photoinduced processes can efficiently lead to the desired optogenetic response(s).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is called as triplet-triplet annihilation (TTA, Scheme 1). [6][7][8][9] By selecting the types of sensitizers and emitters, the wavelengths of the acceptable incident and the generated light can be tuned. [6][7][8][9] Indeed, TTA-supported upconversion systems have been applied for in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] By selecting the types of sensitizers and emitters, the wavelengths of the acceptable incident and the generated light can be tuned. [6][7][8][9] Indeed, TTA-supported upconversion systems have been applied for in vivo imaging. [10][11][12][13][14][15][16] In particular, since UV light, which is favourable for inducing photo-activation into prodrugs, can be generated, TTA-supported upconversion is regarded as a promising tool for realizing phototherapy inside bodies.…”
Section: Introductionmentioning
confidence: 99%